Fabrication and Characterisation of the Cytotoxic and Antibacterial Properties of Chitosan-Cerium Oxide Porous Scaffolds - Lemiha Yildizbakan; Neelam Iqbal; Payal Ganguly; Eric Kumi-Barimah; Thuy Do; Elena Jones; Peter V. Giannoudis; Animesh Jha (MDPI AG, 2023)
Bone damage arising from fractures or trauma frequently results in infection, impeding the healing process and leading to complications. To overcome this challenge, we engineered highly porous chitosan scaffolds (S1, S2, and S3) by incorporating 30 (wt)% iron-doped dicalcium phosphate dihydrate (Fe-DCPD) minerals and different concentrations of cerium oxide nanoparticles (CeO2) (10 (wt)%, 20 (wt)%, and 30 (wt)%) using the lyophilisation technique. The scaffolds were specifically designed for the controlled release of antibacterial agents and were systematically characterised by utilising Raman spectroscopy, X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy methodologies. Alterations in the physicochemical properties, encompassing pore size, swelling behaviour, degradation kinetics, and antibacterial characteristics, were observed with the escalating CeO2 concentrations. Scaffold cytotoxicity and its impact on human bone marrow mesenchymal stem cell (BM-MSCs) proliferation were assessed employing the 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) assay. The synthesised scaffolds represent a promising approach for addressing complications associated with bone damage by fostering tissue regeneration and mitigating infection risks. All scaffold variants exhibited inhibitory effects on bacterial growth against Staphylococcus aureus and Escherichia coli strains. The scaffolds manifested negligible cytotoxic effects while enhancing antibacterial properties, indicating their potential for reducing infection risks in the context of bone injuries.